Hydrocephalus in children. Issue 10020 (20th February 2016) - Kahle, Kristopher T; Kulkarni, Abhaya V; Limbrick, David D; Warf, Benjamin C
Summary: Hydrocephalus is a common disorder of cerebral spinal fluid (CSF) physiology resulting in abnormal expansion of the cerebral ventricles. Infants commonly present with progressive macrocephaly whereas children older than 2 years generally present with signs and symptoms of intracranial hypertension. The classic understanding of hydrocephalus as the result of obstruction to bulk flow of CSF is evolving to models that incorporate dysfunctional cerebral pulsations, brain compliance, and newly characterised water-transport mechanisms. Hydrocephalus has many causes. Congenital hydrocephalus, most commonly involving aqueduct stenosis, has been linked to genes that regulate brain growth and development. Hydrocephalus can also be acquired, mostly from pathological processes that affect ventricular outflow, subarachnoid space function, or cerebral venous compliance. Treatment options include shunt and endoscopic approaches, which should be individualised to the child. The long-term outcome for children that have received treatment for hydrocephalus varies. Advances in brain imaging, technology, and understanding of the pathophysiology should ultimately lead to improved treatment of the disorder.